Muslim Minority in Myanmar: A Case Study of Myanmar Government and Rohingya Muslims - Wekke, Ismail Suardi; Hasbi, Hasbi; Mawardin, M; Ladiqi, Suyatno; Salleh, Mohd Afandi (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2017)
The discrimination suffered by Rohingya Muslims is increasingly blewed up in media in last decade. The peak of the discriminatory treatment against Rohingya Muslim by Myanmar government is the unavailability of shelter from Myanmar government. In the perspective of international law, Myanmar government's actions constitute a serious violence, because it ignores the rights of its citizens. Even a series of massacres and inhumane treatment became a major offense committed by Myanmar government in terms of humanity. This attracted international attention in solving the problem. This article illustrated the fate of Rohingyas who are not given citizenship rights by Myanmar government. It also revealed the irony of Muslims of Rohingya life who are discriminated by the government of Myanmar, both in the practical as well as in the political context.Diskriminasi yang diderita oleh Muslim Rohingya semakin mengemuka di media dalam dekade terakhir. Puncak perlakuan diskriminatif terhadap Muslim Rohingya adalah tidak tersedianya tempat tinggal dari pemerintah Myanmar. Dalam perspektif hukum internasional, tindakan pemerintah Myanmar ini merupakan bentuk kekerasan yang serius, karena mengabaikan hak warganya. Selain itu serangkaian pembantaian dan perlakuan tidak manusiawi menjadi pelanggaran besar yang dilakukan oleh pemerintah Myanmar dalam hal kemanusiaan. Hal ini menarik perhatian dunia internasional dalam upaya memberikan solusi atas permasalahan-permasalahan tersebut. Artikel ini selain menggambarkan nasib warga Rohingya yang tidak diberikan hak kewarganegaraan oleh pemerintah Myanmar, juga mengungkap ironi Muslim dari kehidupan Rohingya yang didiskriminasi oleh pemerintah Myanmar, baik dalam praktik maupun dalam konteks politik.